Automotive industry as a factor of regional competitiveness in the Czech Republic - Rejka, Martin (2016)
The automotive industry is one of the most important industries in the Czech Republic. This diploma thesis identifies its main characteristics and assesses its impact on regional competitiveness. The hypothesis tested in the practical section of this thesis is that suppliers producing high value-added products contribute to regional competitiveness more than suppliers of simple products. A review of relevant theories provides a sound reasoning to support this hypothesis. An analysis of available data from the Czech Republic, however, leads to a rejection of this hypothesis as the results from the practical part signalise that in the Czech Republic the impact of suppliers of simple products is higher than the impact of high value-added suppliers.